Factors Affecting Employee Job Satisfaction at the District Office of Selebar District, Bengkulu City - Hidayatullah, Suryadi; Yulianti, Oni; AbdulRahman , AbdulRahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The aim of the study was to determine factors such as psychological factors, social factors, physical factors and financial factors affecting employee job satisfaction at the Selebar sub-district office, Bengkulu city. The sample in this study was 30 employees at the Selebar District Head Office, Bengkulu City. The sampling technique used in this research is a census because all populations are used as samples. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The research results show a positive direction of regression with the regression equation Y = 4.738 + 0.312X1 + 0.328 X2 + 0.204X3 + 0.284X4. Psychological factors have a positive and significant influence on job satisfaction for employees of the Selebar sub-district office, Bengkulu City, with a significant value of 0.034, less than 0.05. Social factors show a positive and significant influence on job satisfaction for employees of the Selebar sub-district office of Bengkulu City with a significant value of 0.035, less than 0.05. Physical factors show a positive and significant influence on job satisfaction for employees of the Selebar District Office of Bengkulu City with a significant value of 0.025, less than 0.05. The financial factor has a positive and significant influence on job satisfaction in Selebar District Office Employees, Bengkulu City, with a significant value of 0.008, less than 0.05. Psychological factors, social factors, physical factors and financial factors significantly influence job satisfaction in the employees of the Selebar sub-district office of Bengkulu City with a significant value of 0.000, less than 0.05